Conservation opportunities across the world's anthromes. Issue 7 (9th May 2014) - Martin, Laura J.; Quinn, John E.; Ellis, Erle C.; Shaw, M. Rebecca; Dorning, Monica A.; Hallett, Lauren M.; Heller, Nicole E.; Hobbs, Richard J.; Kraft, Clifford E.; Law, Elizabeth; Michel, Nicole L.; Perring, Michael P.; et al.
Abstract Aim Biologists increasingly recognize the roles of humans in ecosystems. Subsequently, many have argued that biodiversity conservation must be extended to environments that humans have shaped directly. Yet popular biogeographical frameworks such as biomes do not incorporate human land use, limiting their relevance to future conservation planning. 'Anthromes' map global ecological patterns created by sustained direct human interactions with ecosystems. In this paper, we set to understand how current conservation efforts are distributed across anthromes. Location Global. Methods We analysed the global distribution of IUCN protected areas and biodiversity hotspots by anthrome. We related this information to density of native plant species and density of previous ecological studies. Potential conservation opportunities in anthromes were then identified through global analysis and two case studies. Results Protected areas and biodiversity hotspots are not distributed equally across anthromes. Less populated anthromes contain a greater proportion of protected areas. The fewest hotspots are found within densely settled anthromes and wildlands, which occur at the two extremes of human population density. Opportunities for representative protection, prioritization, study and inclusion of native species were not congruent. Main conclusions Researchers and practitioners can use the anthromes framework to analyse the distribution of conservation practices at the global and regional scale. Like biomes, anthromes could also be used to set future conservation priorities. Conservation goals in areas directly shaped by humans need not be less ambitious than those in 'natural areas'.